Clinical and microbiological effects of quadrant versus full-mouth root planing-A randomized study - Tanja Predin; Milanko Djuric; Nadja Nikolic; Jelena Mirnic; Ivana Gusic; Djordje Petrovic; Jelena Milasin (Elsevier, 2014)
Background/purpose: Periodontitis is a destructive inflammatory disease of the tooth-supporting tissues caused mainly by Gram-negative microorganisms. Disruption and removal of the subgingival biofilm are the primary objectives of cause-related initial periodontal therapy. The aim of this study was to compare the clinical and microbiological effects after single-visit full-mouth debridement and quadrantwise therapy. Materials and methods: Forty patients diagnosed with chronic periodontitis were randomly assigned to one of the following two treatment protocols: (1) scaling and root planing, quadrant by quadrant, at 1-week intervals and (2) full-mouth scaling and root planing performed in 2 consecutive days. Plaque index, gingival index (GI), papilla bleeding index, probing depth, and clinical attachment level were used to assess the periodontal status of the patients. Polymerase chain reaction was used to determine the presence of Porphyromonas gingivalis, Tannerella forsythia, Prevotella intermedia, and Aggregatibacter actinomycetemcomitans in subgingival plaque. Results: Both treatment modalities resulted in significant clinical improvement, without evident difference between the two groups. Likewise, no differences were detected for selected target bacteria, except for A. actinomycetemcomitans, the level of which was reduced significantly in the full-mouth root planing (FMRP) group (P = 0.007). Conclusion: Results of the present study indicate similar clinical outcomes following both treatment modalities. Although all four species responded more favorably to FMRP, the only statistically significant decrease was recorded in the case of A. actinomycetemcomitans after therapy in this group of patients.